DEVELOPMENT OF THE PROGRAM DIOLAS COMPLEX FOR DIAGNOSTICS IN OFTALMOSKOPY - Запорожець, А.; Верпета, В.; Плюто, І.; Комісаренко, Ю.; Павленко, Ю. (Science-based technologies, 2012)
The paper describes a method and device that allows to study the anterior and posterior parts os the eye in the reflected radiation of the visible and infrared range (not polarized and polarized) using both traditional methods of illumination fundus and innovative technology transscleral ray. For the safety of diagnostic and ophthalmoscopic research in clinical practice, developed a unique software package, based on studies of the International Commission on Non-lonizing Radiation Protection (ICNIRP).